Thesis writing management system - Ypil, Anna Lei Geraldizo (2011)
In the University of the Philippines Mindanao (UPMin), only a few student can graduate on time especially in the BS Computer Science program. One of the reasons for this is the failure of the students to accomplish their Special Problems (SP) on time. Nevertheless, this failure should not, at all time, be seen as the fault of the student alone. Adviser, because of busy schedules, sometimes miss out to check and review the documents submitted by their advisees. As a result, there is a pipeline effects on the scheduling of activities pertinent to the SP. This system is an information system that allows advisers and students to manage and plan in an efficient and organized manner their resources so as to carry successfully the objectives and goals of the project on time. The system allows the monitoring of the progress of thesis projects of students through the Gantt chart. Management of the different files submitted by student is also allowed. The system also enables the tracking of the activities of advisers and students in terms of submissions and checking of files. The administrator of the system is only limited to adviser-advisee assignment as well as approval of user registration. The system is implemented using the Codelgniter framework, while the database is built using MySQL database server.
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2011
Keywords: File management; Database management; University of the Philippines Mindanao (UPMin); BS Computer Science Program; Gantt chart; Special Problems (SP); Codelgniter framework; MySQL database server; User validation; User frames; PHP (Hypertext Preprocessor).